The effects of silver coating on friction coefficient and shear bond strength of steel orthodontic brackets. Issue 4 (21st May 2015) - Arash, Valiollah; Anoush, Keivan; Rabiee, Sayed Mahmood; Rahmatei, Manuchehr; Tavanafar, Saeid
Summary Aims of the present study was to measure frictional resistance between silver coated brackets and different types of arch wires, and shear bond strength of these brackets to the tooth. In an experimental clinical research 28 orthodontic brackets (standard, 22 slots) were coated with silver ions using electroplate method. Six brackets (coated: 3, uncoated: 3) were evaluated with Scanning Electron Microscopy and Atomic Force Microscopy. The amount of friction in 15 coated brackets was measured with three different kinds of arch wires (0.019 × 0.025‐in stainless steel [SS], 0.018‐in stainless steel [SS], 0.018‐in Nickel‐Titanium [Ni‐Ti]) and compared with 15 uncoated steel brackets. In addition, shear bond strength values were compared between 10 brackets with silver coating and 10 regular brackets. Universal testing machine was used to measure shear bond strength and the amount of friction between the wires and brackets. SPSS 18 was used for data analysis with t‐test. SEM and AFM results showed deposition of a uniform layer of silver, measuring 8–10 μm in thickness on bracket surfaces. Silver coating led to higher frictional forces in all the three types of arch wires, which was statistically significant in 0.019 × 0.025‐in SS and 0.018‐in Ni‐Ti, but it did not change the shear bond strength significantly. Silver coating with electroplating method did not affect the bond strength of the bracket to enamel; in addition, it was not an effective method for decreasing friction in sliding mechanics. SCANNING 37:294–299, 2015. © 2015 Wiley Periodicals, Inc.